Toward a resolution of the cosmopolitan Botryllus schlosseri species complex (Ascidiacea, Styelidae): mitogenomics and morphology of clade E (Botryllus gaiae). Issue 4 (31st March 2020) - Brunetti, Riccardo; Griggio, Francesca; Mastrototaro, Francesco; Gasparini, Fabio; Gissi, Carmela
Abstract: Botryllus schlosseri is a model colonial ascidian and a marine invader. It is currently recognized as a species complex comprising five genetically divergent clades, with clade A globally distributed and clade E found only in Europe. This taxon has also been recently redescribed by designation of a clade A specimen as the neotype. To clarify the taxonomic status of clade E and its relationship to clade A, we examine the entire mitochondrial genome and study the morphology of clade E. The mitogenome of clade E has an identical gene order to clade A, but substantially differs in the size of several non-coding regions. Remarkably, the nucleotide divergence of clade A-clade E is incompatible with the intraspecies ascidian divergence, but similar to the congeneric one and almost identical to the divergence between species once considered morphologically indistinguishable (e.g. the pair Ciona intestinalis (Linnaeus, 1767)- Ciona robusta Hoshino & Tokioka, 1967, and the pair Botrylloides niger Herdman, 1886- Botrylloides leachii (Savigny, 1816)). Clade E differs morphologically from the Botryllus schlosseri neotype mainly in the number and appearance of the stomach folds, and the shape of the anal opening, the first intestinal loop and the typhlosole. Our integrative taxonomical approach clearly distinguishes clade E as a species separate from Botryllus schlosseri, with unique morphological and molecular characters. Therefore, we here describe clade E as the new species Botryllus gaiae sp. nov.